2008
DOI: 10.1142/s0218810408003736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Result of Operative Treatment for Scaphoid Non-Union in the Skeletally Immature: Percutaneous Versus Open Procedure

Abstract: This article is a retrospective study of 13 cases of scaphoid non-union in skeletally immature patients. For the fracture fixation, three cases of stable fibrous union with minimal sclerosis, without deformity or cystic changes were considered for the percutaneous Herbert screw fixation. Ten cases were managed with the open reduction and internal fixation with or without bone grafting. The average union time was 10.5 weeks post-operatively. The average union time was lesser in percutaneous Herbert screw fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The natural history of pseudarthrosis of the scaphoid in immature skeletons is unknown. The biomechanical alterations seen in the wrists of adults have not yet been reported in children 8 , 9 , 10 . A differential diagnosis need to be made with bipartite scaphoid, which is usually bilateral, asymptomatic and unrelated to previous trauma.…”
Section: Introductionmentioning
confidence: 93%
“…The natural history of pseudarthrosis of the scaphoid in immature skeletons is unknown. The biomechanical alterations seen in the wrists of adults have not yet been reported in children 8 , 9 , 10 . A differential diagnosis need to be made with bipartite scaphoid, which is usually bilateral, asymptomatic and unrelated to previous trauma.…”
Section: Introductionmentioning
confidence: 93%
“…This classification provides a guide for surgeons regarding the type of treatment to use (1,8,9,12) (Figure 1). (12) .…”
Section: Classificationmentioning
confidence: 99%
“…They may also be complemented by specific views for the scaphoid (8,9,13) . Masquijo and Willis (1) reported that the presence of sclerosis, cystic formations and bone reabsorption define pseudarthrosis on radiographic images.…”
Section: Diagnosis Through Imagingmentioning
confidence: 99%
See 2 more Smart Citations